An Overview of The Eye Component (Iris, Lens and Retina) From Mackerel Female (Rastrelliger brachysoma) - Kiki Fiolita (UNIVERSITAS NEGERI PADANG, 2017)
Fish ability to exist and defend their lifeinvolve sense of sight beside sense or another receptors. One of thefactor that influence fish behavior is the sight sharpness. Which is influence by amount and cell formation of cone cells, rod cells, and eye lens diameter. In Indonesia, comprehension and study about the fish sight ability is still minimal in fact this study is very important for fishery technology development. This research aims to describeof theeye components (Iris, Lens, and Retina). This research observe the component eye mackerel female.This research is descriptive, that is reveals research object data actually. Research which observe the component of femalemackerelseye. Theeyes component which is taken is iris, lens, and retina, and the observation use Scanning Electron Microscope (SEM).The results indicate that iris structure of the fish contain a lot of melanosoms pigment. The lens have the rounds shape and transparant yellows color, the retina have cone cell and rod cell. The conecell from sided mozaik also have two cells types, singular and doubled cone cells. The is due to mackerel high intensity in using their sense of sight, ability to distinguish colors and including fish that actively hunt prey. Keywords Rastrellige brachysoma, the structure of fish eyes, photoreceptors.